Analysis of implementing the Ukrainian healthcare reform in 2023 - Nataliia Sheliemina (Health Economics and Management Review)
The main research task is to study the issue of effectiveness of implementing the healthcare reform in Ukraine using the main levers of influence on the most significant items of expenditure in the medical industry itself. Also, we investigate the main items of income and expenses of medical service providers, their specific weight and management methods for more rational use. It is worth noting that the positive dynamics in the direction of effectiveness of the healthcare industry is not only the main priority. It is also a direct tool that drives the general processes in the medical industry. Increasing the level of social protection is one of the primary goals of medicine and, as a result, improving the quality of state population life. In a chain reaction, this will lead to a reduction in costs for the healthcare industry due to faster recovery of patients and reduction of time spent in a state of temporary incapacity. One of the key aspects of the medical reform efficiency remains the issue of remuneration of workers. Before carrying out reform measures, doctor salaries were officially at the minimum level. Therefore, the principle of treatment for the patient’s money was widespread in the industry. The main motivating element of the human capital efficiency is salary – reward for work results. So, if the salary directly depends on the target indicators that must be achieved in the production process, then the employee’s motivation increases. Based on the fact that the main direction of funds expenditure at medical institutions is labour costs, the main efforts and attention should be paid in the organisational and administrative plan to work with the effective use of this item of expenses. It is worth noting that the salary of any employee is the main measure of his work efficiency. It is a motivator to improve the quality and treatment efficiency. If the amount of reward depends on the employee’s performance indicators, the system will have additional motivation not only in the quantitative characteristics of the work result, but also in the qualitative parameters.